Levels and Prevalence of Mental Health Functioning in Canadian University Student-Athletes - Van Slingerland, Krista J.; Durand-Bush, Natalie; Rathwell, Scott (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2018)
We examined the level and prevalence of mental health functioning (MHF) in intercollegiate student-athletes from 30 Canadian universities, and the impact of time of year, gender, alcohol use, living situation, year of study, and type of sport on MHF. An online survey completed in November 2015 (N = 388) and March 2016 (n = 110) revealed that overall, MHF levels were moderate to high, and more student-athletes were flourishing than languishing. MHF levels did not significantly differ across time based on gender, alcohol use, living situation, year of study, and type of sport. Eighteen percent reported a previous mental illness diagnosis and yet maintained moderate MHF across time. These findings support Keyes’ (2002) dual-continua model, suggesting that the presence of mental illness does not automatically imply low levels of well-being and languishing. Nonetheless, those without a previous diagnosis were 3.18 times more likely to be flourishing at Time 1 (November 2015).